The psychological peculiarities of young learners for teaching foreign languages (Eurasian Scientific Herald, 2023)
This article is written that it is very important to know the psychological peculiarities of young learners For the successful teaching of English in schools, it is essential for the teacher to understand the young learners characteristics and interests, because this plays a crucial role in how the teacher builds a lesson, how he or she can make sure that the young learners are fully involved in the learning process, how he or she achieves the objectives of a lesson, and how they respond. Psychological peculiarities of young learners are describing in this work.